How professional identity shapes youth healthcare. Issue 3 (18th May 2015) - Dadich, Ann; Jarrett, Carmen; Robards, Fiona; Bennett, David
Abstract : Purpose: – The primary care sector is experiencing considerable change. How change and uncertainty are accommodated by the professional identity of medicine has not been examined. The purpose of this paper is to address the youth healthcare as an exemplar as this field is often a source of uncertainty for general practitioners (GPs). Design/methodology/approach: – Using heterogeneity sampling, 22 GPs participated in focus groups to explore perceptions of youth healthcare, factors that help and hinder it, and training needs. Analysis of the research material was guided by a theoretical model on professional identity. Findings: – GPs described tensions that challenged their professional identity – the challenges of working with young people and their complex issues, the extent to which youth healthcare sits within the purview of general practice, and the scope of training required. These tensions appeared to destabilise professional identity. Some participants had customised their identity by enriching understandings of and approach to general practice. Participants also reported work customisation as a way of managing the complex demands of the general practice role. Deepened insight appeared to bolster perceived capacity to support a complex patient cohort. Research limitations/implications: – Participants are not representative of the primary care sector – furthermore, the methodology limits the generalisability of the findings. Practical implications: – To bolster youth health, mere clinician training is insufficient. Youth health requires explicit support from governments and training providers to be incorporated into the healthcare landscape. Originality/value: – This study extends current research on professional identity by examining youth healthcare within the changing context of primary care.